Aphrodisiac properties and toxicological evaluation of Aquilaria malaccensis and Aquilaria subintegra (Agarwood) leaves Aqueous extract in ICR Mice - Nur Hidayat Che Musa (2019)
This study aimed to investigate the properties of aphrodisiac and to evaluate thetoxicological effect of leaves aqueous extract from Aquilaria malaccensis (AEAM)and Aquilaria subintegra (AEAS) against ICR mice. The aphrodisiac properties,which include sexual behaviour, orientation activity, number of offspring, male tofemale ratio of offspring, the percentage of pregnancy and testosterone level.Meanwhile, toxicological evaluation consists of acute and sub-acute study. Inaphrodisiac study, the treated groups received 50, 100, 200, 500, and 1000 mg/kgbody weight (b.w.) of extracts for 21 consecutive days. In acute toxicity study, thetreated animals received a single dose at 2000 mg/kg b.w., while in sub-acute toxicitystudy, the treated groups received 50, 100, 150, 200, 500, and 1000 mg/kg b.w. ofextracts for 21 consecutive days compared to control groups that received normalsaline only. Statistical analyses were performed using t-test and one-way ANOVAand also considered significantly different at p0.05) in sexual behaviour and orientation activity of treated mice ascompared to the controls. The treatment groups that received higher doses (500 and1000 mg/kg) of both extracts found to be inactive due to the sedative effect. However,higher aphrodisiac properties were displayed by AEAM treated mice compared toAEAS. The number of offspring in AEAS was higher compared to AEAM.Toxicological evaluation showed that there was a significant increase (p